Bilateral lungs uptake of 99mTc-HDP in a post treated patient with breast carcinoma - Yadav, Ajay Kumar; Ray, Raj Narayan; Joshi, Swechchha; Ansari, Quamrul Haque; Gengbiao, YUAN (Nepalese Journal of Cancer, 2018)
99mTc-HDP radiopharmaceuticals uptake has been reported at various sites and it is known to be induced by various causes. Bilateral lungs uptake of 99mTc-HDP in a post treated patient with breast carcinoma can be a cause of poor renal function as chemotherapy affects renal function. Here we report on a post treated patient with Ca Breast in which rarely having 99mTc-HDP uptake in bilateral lungs. After full cycle of chemotherapy treatment, some patient suffer with poor renal function although it will improve along with time but due to poor renal function there is chance of 99mTc-HDP uptake in lungs during bone Scintigraphy. So Bilateral lungs uptake of 99mTc-HDP in a post treated patient with breast carcinoma on bone scan may suggest rare but due to poor renal function which some time develop after full cycle chemotherapy treatment.